2018
DOI: 10.1148/radiol.2018180137
|View full text |Cite
|
Sign up to set email alerts
|

CT Detectability of Small Low-Contrast Hypoattenuating Focal Lesions: Iterative Reconstructions versus Filtered Back Projection

Abstract: Purpose To investigate performance in detectability of small (≤1 cm) low-contrast hypoattenuating focal lesions by using filtered back projection (FBP) and iterative reconstruction (IR) algorithms from two major CT vendors across a range of 11 radiation exposures. Materials and Methods A low-contrast detectability phantom consisting of 21 low-contrast hypoattenuating focal objects (seven sizes between 2.4 and 10.0 mm, three contrast levels) embedded into a liver-equivalent background was scanned at 11 radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…No NPS peak shift occurred using IIR, except for 2.5 mGy, whereas the NPS peak of ADMIRE shifted by 20%-30% compared to FBP, confirming the values reported by Christianson et al9 The peak shift causes an unnatural image texture9,14,15 and may alter the search pattern and image perception of radiologists. 6.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…No NPS peak shift occurred using IIR, except for 2.5 mGy, whereas the NPS peak of ADMIRE shifted by 20%-30% compared to FBP, confirming the values reported by Christianson et al9 The peak shift causes an unnatural image texture9,14,15 and may alter the search pattern and image perception of radiologists. 6.…”
supporting
confidence: 84%
“…This trend was more remarkable when using the stronger ADMIRE 5. The peak shift causes an unnatural image texture 9,14,15 and may alter the search pattern and image perception of radiologists. 14 Therefore, IIR images might have greater clinical acceptability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical iterative reconstruction has several potential advantages and has been implemented specifically for the purpose of dose reduction. The dose reduction possible from SIR varies with the study . Unfortunately, automated methods for assessing dose reduction are difficult and traditional MTF and NPS metrics are not useful .…”
Section: Introductionmentioning
confidence: 99%
“…The dose reduction possible from SIR varies with the study. [4][5][6] Unfortunately, automated methods for assessing dose reduction are difficult and traditional MTF and NPS metrics are not useful. 7 Clinical studies comparing SIR to filtered backprojection (FBP) have shown an advantage for SIR at very low doses.…”
Section: Introductionmentioning
confidence: 99%